Massive cerebral infarction after completion pneumonectomy for pulmonary torsion. - Hendriks, J. (1994)
A case of lower lobe torsion after left upper lobectomy is reported which was complicated by a cerebral infarction after completion pneumonectomy. Results of a small survey in Flanders revealed two additional cases of pulmonary torsion after lobectomy.